Analisis Penyediaan Air Bersih (Studi kasus: Desa Poni-poniki, Kec. Tirawuta, Kab. Kolaka Timur) - Ramjan Ramjan; Romi Talanipa; Rini Sriyani; Muh. Handy Dwi Adityawan (PRODI D3 TEKNIK SIPIL, 2023)
AbstractAlong with the growth of the community, the water demand in Poni-Poniki Village is increasing, but it is not balanced with the development of existing clean water management facilities. The purpose of this study was to determine the availability of clean water in the village of poni-poniki, by measuring the discharge of the springs in the mountains of Poni-poniki. Then analyze the need for clean water based on survey data and the results of population projection analysis. Based on the real demand survey (RDS), the water needs of the people of Poni-poniki Village in 2019 = 0.840 liters/second, and in 2023 = 0.993 liters/second. Mountain spring discharge based on field measurements using the Volumetric method is 0.00347 m³/second or 3.467 liters/second. Thus, the availability of water until 2023 can still be met safely, but the water sources used will not meet the needs in the next few years.AbstrakSeiring dengan pertumbuhan masyarakat maka kebutuhan air di Desa Poni-Poniki semakin meningkat namun tidak diimbangi dengan pengembangan sarana pengelolahan air bersih yang ada. Tujuan dari penelitian ini untuk mengetahui ketersediaan air bersih desa poni-poniki, dengan melakukan pengukuran debit mata air pegunungan Poni-poniki. Kemudian menganalisis kebutuhan air bersih berdasarkan data hasil survey dan hasil analisis proyeksi penduduk. Berdasarkan real demand survey (RDS), kebutuhan air masyarakat Desa Poni-poniki pada tahun 2019 = 0,840 ltr/dtk, dan tahun 2023 = 0,993 ltr/detik. Debit Mata Air pegunungan berdasarkan pengukuran dilapangan menggunakan metode Volumetrik adalah 0.00347 m³/detik atau 3.467 liter/detik. Dengan demikian ketersediaan air sampai tahun 2023 masih dapat terpenuhi dengan aman, tetapi sumber air yang digunakan tidak memenuhi kebutuhan dalam beberapa tahun mendatang.